2018
DOI: 10.5194/tc-12-759-2018
|View full text |Cite
|
Sign up to set email alerts
|

The European mountain cryosphere: a review of its current state, trends, and future challenges

Abstract: Abstract. The mountain cryosphere of mainland Europe is recognized to have important impacts on a range of environmental processes. In this paper, we provide an overview on the current knowledge on snow, glacier, and permafrost processes, as well as their past, current, and future evolution. We additionally provide an assessment of current cryosphere research in Europe and point to the different domains requiring further research. Emphasis is given to our understanding of climate–cryosphere interactions, cryos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
377
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 482 publications
(392 citation statements)
references
References 371 publications
(426 reference statements)
12
377
0
3
Order By: Relevance
“…Studies have generally reported declining Northern Hemisphere snow cover duration where a clear trend exists (e.g., Brown, ; Durand et al , ; Choi et al , ; Marty et al , ; Beniston et al , ). Negative trends are predominantly from lower elevations, suggesting threshold effects exist related to the combined effect of temperature and precipitation on snowfall quantities as they co‐vary across both altitude (based upon the lapse rate) and latitude/longitude (Stewart, ; Fontrodona Bach et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have generally reported declining Northern Hemisphere snow cover duration where a clear trend exists (e.g., Brown, ; Durand et al , ; Choi et al , ; Marty et al , ; Beniston et al , ). Negative trends are predominantly from lower elevations, suggesting threshold effects exist related to the combined effect of temperature and precipitation on snowfall quantities as they co‐vary across both altitude (based upon the lapse rate) and latitude/longitude (Stewart, ; Fontrodona Bach et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the world's major mountain ranges are underlain by permafrost (e.g.,), and mountain permafrost can exert an important control on earth system processes and engineering designs . Under recent climate change, mountain permafrost is degrading, leading to increased slope failure events and potential changes in hydrological regimes . However, the distribution of permafrost in mountainous regions is complicated by factors generally not encountered in low‐relief permafrost areas, including steep topography, deep snowpacks, and coarse blocky sediments (e.g., ).…”
Section: Introductionmentioning
confidence: 99%
“…While our results suggest a link between warm temperatures and adult survival in female alpine chough, their survival did not show a clear negative trend (Figure ). The rate of warming in the region involved a +1.2°C mean temperature increase over the timespan of the study (Beniston et al, ; Ceppi, Scherrer, Fischer, & Appenzeller, ; Rangwala & Miller, ), which is one of the most intense warming rates for mountains in the world, but might not be enough to result in a clear trend in adult female survival given the 6°C variation of mean winter/spring temperatures in the different years of the study (Figure in Appendix ). High‐elevation regions are expected to experience more intense warming than lowlands over the 21st century (Pepin et al, ; Rangwala & Miller, ), as was the case in the 20th century.…”
Section: Discussionmentioning
confidence: 99%